IMPLEMENTASI PROGRAM RUMAH DATA KEPENDUDUKAN DALAM MENINGKATKAN PENGELOLAAN DATA DI LEVEL MIKRO - Hanifah, Inas Nur; Samsuharjo, Samsuharjo (PARADIGMA: Jurnal Ilmu Administrasi, 2024)
The Population Data House, commonly referred to as Rumah DataKu, is one of the key success factors of the Kampung KB program. The aim of this study is to understand how the implementation of the Population Data House program enhances data management in the Kampung KB Teratai Kalurahan Tileng area and to identify the supporting and inhibiting factors of the program's implementation. The method used in this study is a descriptive qualitative method with research indicators based on the policy implementation approach model by George C. Edward III. Data collection methods include interviews, observations, and documentation. To test the validity of the data, source triangulation and technique triangulation methods were used. The qualitative data analysis starts from data collection, data simplification, data presentation, and conclusion drawing. The results of this study are based on four indicators: (1) Initial communication was quite good, as seen from the coordination with all parties involved in the program implementation. However, the program's socialization only reached a portion of the community. (2) Resources consist of two subcategories: human resources and budget resources. In the implementation of the RDK program, human resources were still inadequate, while budget resources were limited. (3) The disposition and attitude of the implementers were quite good, with a strong commitment to their duties and responsibilities. (4) The bureaucratic structure in the program implementation was supported by SOPs and an organizational structure that effectively carried out the assigned activities.Keyword: Implementation Program; Population Data House; Kalurahan Tileng.